Adverse drug reactions and contributing factors in patients with drug-resistant tuberculosis: A 7-year retrospective cohort study in Addis Ababa, Ethiopia - Bisrat Solomon; Yimtubezinash Woldeamanuel; Tigest Ajeme; Mbazi Senkoro; Tsegahun Manyazewal (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Drug-resistant tuberculosis poses a major global public health threat, with adverse drug reactions complicating treatment and contributing to mortality. In Ethiopia, although many patients with drug-resistant tuberculosis are receiving treatment, studies on adverse drug reactions and their contributing factors remain limited. This study aimed to assess the incidence of adverse drug reactions and contributing factors in patients on drug-resistant tuberculosis treatment in Addis Ababa, Ethiopia. Methods: A facility-based, retrospective cohort study was conducted on patients with drug-resistant tuberculosis who were followed up in two major drug-resistant tuberculosis treatment sites, St. Peter’s Specialized Hospital and the ALERT Comprehensive Specialized Hospital, in the years of 2017 to 2023. Records of the patients were reviewed throughout their treatment time. Information on any adverse drug reaction diagnosis, laboratory findings, clinical observations, type of second-line regimen, type and nature of the drug-resistant tuberculosis, presence of comorbidities such as Human Immune deficiency Virus, hypertension, diabetes mellitus, chronic obstructive pulmonary diseases, and asthma, and sociodemographic characteristics were abstracted from patients’ charts and registries. The World Health Organization − Uppsala Monitoring Center (WHO-UMC) system was employed for standardized causality assessment of adverse drug reactions. Multivariate Cox regression analysis was employed to identify factors associated with adverse drug reactions. Survival among predictor variables was assessed using Kaplan-Meier (KM) curves. Adjusted hazard ratios (AHR) with their corresponding 95 % confidence intervals (CI) were estimated, and statistical significance was declared for a p-value < 0.05. Result: A total of 292 patients with drug-resistant tuberculosis were included. The overall incidence of adverse drug reaction was 8.10 per 100 person-month (PM) (95 % CI: 7.02–9.36) during a total follow-up time of 2294 months. The most frequently reported adverse drug reactions were gastrointestinal disturbance (31.9 %), followed by peripheral neuropathy (21.9 %), and arthralgia (17.5 %). Factors associated with adverse drug reactions were hospitalization (AHR = 1.53, 95 % CI: 1.10–2. 13), baseline anemia (AHR = 1.58, 95 % CI: 1.16–2.17), the age group of 25–49 years (AHR = 1.53, 95 % CI: 1.05–2.21), and age greater than or equal to 50 years (AHR = 1.87, 95 % CI: 1.19–2.93). Good treatment outcome was observed in 76 % of cases. Conclusion: In this study involving patients with drug resistant tuberculosis, over half of the participants encountered at least one adverse drug reactions. Patient admission, baseline anemia, and older age were identified as major factors associated with adverse drug reaction during multidrug resistant tuberculosis treatment. Particular emphasis should be placed on these susceptible groups to facilitate early prediction, prompt management, and the formulation of appropriate treatment regimens that address adverse drug reactions effectively.